Head-Elevated Patient Positioning Decreases Complications of Emergent Tracheal Intubation in the Ward and Intensive Care Unit - Khandelwal, Nita; Khorsand, Sarah; Mitchell, Steven H; Joffe, Aaron M (Anesthesia and analgesia, 2016)
Based on the data from elective surgical patients, positioning patients in a back-up head-elevated position for preoxygenation and tracheal intubation can improve patient safety. However, data specific to the emergent setting are lacking. We hypothesized that back-up head-elevated positioning would be associated with a decrease in complications related to tracheal intubation in the emergency room environment. This retrospective study was approved by the University of Washington Human Subjects Division (Seattle, WA). Eligible patients included all adults undergoing emergent tracheal intubation outside of the operating room by the anesthesiology-based airway service at 2 university-affiliated teaching hospitals. All intubations were through direct laryngoscopy for an indication other than full cardiopulmonary arrest. Patient characteristics and details of the intubation procedure were derived from the medical record. The primary study endpoint was the occurrence of a composite of any intubation-related complication: difficult intubation, hypoxemia, esophageal intubation, or pulmonary aspiration. Multivariable logistic regression was used to estimate the odds of the primary endpoint in the supine versus back-up head-elevated positions with adjustment for a priori-defined potential confounders (body mass index and a difficult intubation prediction score [Mallampati, obstructive sleep Apnea, Cervical mobility, mouth Opening, Coma, severe Hypoxemia, and intubation by a non-Anesthesiologist score]). Five hundred twenty-eight patients were analyzed. Overall, at least 1 intubation-related complication occurred in 76 of 336 (22.6%) patients managed in the supine position compared with 18 of 192 (9.3%) patients managed in the back-up head-elevated position. After adjusting for body mass index and the Mallampati, obstructive sleep Apnea, Cervical mobility, mouth Opening, Coma, severe Hypoxemia, and intubation by a non-Anesthesiologist score, the odds of encountering the primary endpoint during an emergency tracheal intubation in a back-up head-elevated position was 0.47 (95% confidence interval, 0.26-0.83; P = 0.01). Placing patients in a back-up head-elevated position, compared with supine position, during emergency tracheal intubation was associated with a reduced odds of airway-related complications.